Electrode material, preparation method thereof and flow battery
By using a combination method of tannin acid and metal salt in the liquid flow battery electrode material, the problem of low fixation efficiency of metal nanocatalysts in the electrode material is solved, and efficient preparation of electrode materials and improvement of liquid flow battery performance is achieved.
Patent Information
- Application Number
- CN202411466118.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The metal nanocatalysts of existing flow battery electrode materials have low fixation efficiency, complex preparation process, long high temperature processing time, high cost and poor circulation performance, which limit large-scale applications.
By mixing tannin acid with organic solvent, soaking the electrode substrate, then adding metal salt, mixing and drying, and finally sintering, stable fixation of the metal nanocatalyst is achieved.
This method simplifies the preparation process of electrode material, reduces fixed costs and time, improves fixed efficiency, improves the stability and catalytic effect of electrode material, and significantly improves the electrochemical performance of the flow battery.
Smart Images

Figure CN119008982B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of energy storage batteries, and in particular relates to an electrode material, a preparation method thereof and a liquid flow battery. Background Art
[0002] The use of renewable energy such as solar energy and wind energy has become more and more widespread, but solar energy and wind energy have problems such as intermittency and volatility in power generation. Large-scale energy storage technology can solve the above problems, ensure the smooth output of renewable energy power generation, and promote the large-scale, continuous and stable use of renewable energy. As a large-scale energy storage technology, flow batteries have a series of advantages, such as good safety, long service life, high reliability, independent adjustment of power and capacity, etc., which can effectively solve the intermittent and volatility problems of renewable energy such as solar energy and wind energy in power generation. As a key component of flow batteries, the performance of electrodes directly affects the final performance of the battery. At present, the commonly used flow battery electrode materials have low reversibility and poor electrochemical performance, which seriously affect the performance of flow batteries. Loading nanocatalysts on the surface of porous carbon material electrodes can effectively solve these problems.
[0003] At present, the common methods for fixing metal nanocatalysts on the surface of flow battery electrodes are mainly the following methods. Hosseini et al. introduced nitrogen and tungsten trioxide onto the surface of carbon felt by a hydrothermal method, but the preparation method is relatively complicated and requires an autoclave reactor (see MG Hosseini, et al., Carbon, 2018, 136,444.); Zhang et al. prepared uniformly distributed Sb-doped nanoparticles on carbon paper by electrodeposition and in situ oxidation, but the preparation steps of this method are cumbersome and the preparation process requires complex equipment such as a three-electrode system and an electrochemical workstation (see R. Zhang, et al., Applied Surface Science, 2020, 526, 146685.); Patent document CN112054215A discloses a bismuth salt carbon thermal reduction method for preparing electrode materials with a high-temperature treatment time of 150 min and a cycle number of 500 times; Patent document CN118099459A discloses a reduction method for preparing electrode materials with a high-temperature treatment time of 180 min and a cycle number of 100 times.
[0004] In summary, the existing method of fixing metal nanocatalysts on the surface of liquid flow battery electrodes to prepare electrode materials is relatively complicated to operate, the high-temperature treatment time is long, the cost of fixing the metal nanocatalysts is high, and the cycle performance of the prepared electrode materials is poor, which is not conducive to large-scale application.
[0005] Therefore, there is an urgent need to develop a method for preparing liquid flow battery electrode materials with excellent electrochemical performance, simple preparation process, short preparation time and low preparation cost. Summary of the invention
[0006] In order to solve the deficiencies in the prior art, the present invention provides a method for preparing an electrode material, wherein the metal nanocatalyst on the electrode material prepared by the method has high fixing efficiency, high stability of the electrode material, good catalytic effect, and excellent electrochemical performance of a flow battery assembled with the electrode material prepared by the method, and the method has a simple preparation process and low cost. The method of the present invention can universally and stably fix the metal nanocatalyst on the surface of the flow battery electrode. In summary, the method for preparing the electrode material of the present invention is easy to promote and apply, and is conducive to large-scale application.
[0007] Specifically, the present invention provides a method for preparing an electrode material, the method comprising the following steps:
[0008] (1) mixing tannic acid and an organic solvent to prepare a tannic acid solution;
[0009] (2) soaking the electrode substrate in the tannic acid solution prepared in step (1), evacuating and degassing the solution, and then mixing the solution to load the tannic acid on the electrode substrate;
[0010] (3) adding the metal salt to the reaction system obtained in step (2), first performing the first step of mixing to dissolve the metal salt, then performing vacuuming and degassing, and then performing the second step of mixing, and then taking out the electrode substrate loaded with the coating precursor and drying it to obtain an electrode material intermediate, wherein the coating precursor is formed by the reaction of the metal salt and tannic acid;
[0011] (4) Sintering the electrode material intermediate obtained in step (3) to obtain an electrode material.
[0012] In one or more embodiments, in step (1), the organic solvent is selected from one or more of ethylene glycol, ethanol, acetone, N,N-dimethylformamide, dichloroethane and chloroform.
[0013] In one or more embodiments, in step (1), the mass ratio of the organic solvent to tannic acid is (1-100):1.
[0014] In one or more embodiments, in step (1), the mixing method is selected from one or more of ultrasound, stirring and shaking.
[0015] In one or more embodiments, in step (1), the mixing time is 1 to 120 minutes.
[0016] In one or more embodiments, in step (2), the electrode substrate is carbon felt, graphite felt, carbon cloth, carbon paper or foamed carbon.
[0017] In one or more embodiments, in step (2), the vacuuming time is 1 to 120 minutes.
[0018] In one or more embodiments, in step (2), the mixing method is selected from one or more of ultrasound, stirring and shaking.
[0019] In one or more embodiments, in step (2), the mixing time is 1 to 120 minutes.
[0020] In one or more embodiments, in step (3), the metal salt is selected from one or more of a silver salt, a bismuth salt, an iridium salt and a platinum salt.
[0021] In one or more embodiments, in step (3), the molar ratio of the metal ion in the metal salt to the tannic acid in step (1) is (5-9):1.
[0022] In one or more embodiments, in step (3), the first mixing method is selected from one or more of ultrasound, stirring and shaking.
[0023] In one or more embodiments, in step (3), the first step mixing time is 1 to 120 minutes.
[0024] In one or more embodiments, in step (3), the vacuuming time is 1 to 120 minutes.
[0025] In one or more embodiments, in step (3), the second mixing method is selected from one or more of ultrasound, stirring and shaking.
[0026] In one or more embodiments, in step (3), the second mixing time is 1 to 120 minutes.
[0027] In one or more embodiments, in step (3), the drying temperature is 40-400°C.
[0028] In one or more embodiments, in step (3), the drying time is 20 to 720 minutes.
[0029] In one or more embodiments, in step (4), sintering is performed in an atmosphere of nitrogen or an inert gas.
[0030] In one or more embodiments, in step (4), the heating rate of the sintering process is 1-50° C. / min.
[0031] In one or more embodiments, in step (4), the sintering temperature is 200-800°C.
[0032] In one or more embodiments, in step (4), the sintering time is 0.5 to 3 hours.
[0033] In one or more embodiments, in step (4), the inert gas is selected from one or more of argon, helium, xenon and neon.
[0034] In one or more embodiments, in step (4), the flow rate of nitrogen or inert gas is 1-500 mL / min.
[0035] The present invention also provides an electrode material prepared by the method of the present invention.
[0036] In one or more embodiments, metal nanoparticles are present on the surface of the electrode material.
[0037] The present invention also provides a liquid flow battery comprising the electrode material of the present invention.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. In the present invention, since the phenolic hydroxyl group of tannic acid can reduce the metal catalyst ions and stably fix them on the electrode carbon felt, the present invention can fix the metal nanocatalyst on the electrode substrate by simply soaking in a solution; the present invention has very simple steps, reduces the fixing cost, shortens the fixing time, and effectively improves the fixing efficiency;
[0040] 2. In the present invention, since the phenolic hydroxyl group in tannic acid has strong reducing property, the present invention can realize the loading of metal nanocatalyst on the electrode substrate without using any auxiliary reducing agent. The present invention is applicable to metal catalysts with catalytic effect such as silver, bismuth, platinum, iridium, etc.;
[0041] 3. The electrode material prepared by the method of the present invention has high stability and good catalytic effect, and can significantly improve the performance of liquid flow batteries;
[0042] 4. The steps of the present invention are very simple, and no expensive instruments are needed. Conventional instruments can be used to load the metal nanocatalyst on the surface of the electrode carbon felt, which is low in cost and suitable for large-scale applications;
[0043] 5. The reaction conditions of the present invention are simple and mild, and can be achieved using conventional instruments without the need to use special experimental reagents and expensive instruments. Therefore, the method of the present invention is easy to promote and apply, and is conducive to large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a low-magnification scanning electron microscope image of the electrode material prepared in Example 2.
[0045] Figure 2 This is a lower magnification scanning electron microscope image of the electrode material prepared in Example 2.
[0046] Figure 3 This is a high-magnification scanning electron microscope image of the electrode material prepared in Example 2.
[0047] Figure 4 This is a scanning electron microscope image of the electrode material prepared in Example 2.
[0048] Figure 5 This is the X-ray energy spectrum of the electrode material prepared in Example 2. DETAILED DESCRIPTION
[0049] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this document. Unless otherwise specified, all technical and scientific terms used in this document have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.
[0050] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0051] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0052] In this document, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values within the range (including integers and fractions).
[0053] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0054] Herein, when describing embodiments or examples, it should be understood that it is not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope defined herein.
[0055] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0056] The present invention provides a method for preparing an electrode material, the method comprising the following steps:
[0057] (1) mixing tannic acid (TA) and an organic solvent to prepare a tannic acid solution;
[0058] (2) soaking the electrode substrate in the tannic acid solution prepared in step (1), evacuating and degassing the solution, and then mixing the solution to load the tannic acid on the electrode substrate;
[0059] (3) adding the metal salt to the reaction system obtained in step (2), first performing the first step of mixing to dissolve the metal salt, then performing vacuuming and degassing, and then performing the second step of mixing, and then taking out the electrode substrate loaded with the coating precursor and drying it to obtain an electrode material intermediate, wherein the coating precursor is formed by the reaction of the metal salt and tannic acid;
[0060] (4) Sintering the electrode material intermediate obtained in step (3) to obtain an electrode material.
[0061] In step (1) of the present invention, the purpose of mixing the tannic acid mixed solution is to effectively dissolve the tannic acid; in step (2) of the present invention, the purpose of vacuuming is to allow the tannic acid mixed solution to fully immerse into the electrode substrate; in step (2) of the present invention, the purpose of mixing is to allow the tannic acid mixed solution to be more evenly distributed on the flow battery electrode; in step (3) of the present invention, the purpose of vacuuming is to allow the mixed solution to fully immerse into the electrode substrate; in step (3) of the present invention, the purpose of the second step of mixing is to allow the metal nanoparticles to be evenly distributed in the electrode.
[0062] In the present invention, steps (1) and (2) are to obtain an electrode material precursor in which tannic acid is coated on an electrode substrate; step (3) adds a metal salt and utilizes the reduction characteristics of the tannic acid coated on the electrode substrate to in-situ reduce the metal particles to obtain an electrode material intermediate; step (4) sinters the electrode material intermediate obtained in step (3) to obtain an electrode material. Preparing the electrode material according to the preparation sequence proposed in the present invention is conducive to improving the voltage efficiency, energy efficiency, charge and discharge energy and cycle performance of the liquid flow battery.
[0063] In step (1), the organic solvent may be one or more selected from ethylene glycol, ethanol, acetone, N,N-dimethylformamide, dichloroethane and chloroform.
[0064] In step (1), the mass ratio of the organic solvent to tannic acid can be (1-100):1, for example, 1:1, 5:1, 10:1, 15:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1.
[0065] In step (1), the mixing method can be one or more selected from ultrasound, stirring and oscillation. In some embodiments, ultrasound is used for dissolution.
[0066] In step (1), the mixing time can be 1 to 120 min, for example, 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min.
[0067] In step (2), the electrode substrate may be carbon felt, graphite felt, carbon cloth, carbon paper or foamed carbon.
[0068] In step (2), the vacuuming time can be 1 to 120 min, for example, 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min.
[0069] In step (2), the mixing method can be one or more selected from ultrasound, stirring and oscillation.
[0070] In step (2), the mixing time can be 1 to 120 min, for example, 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min.
[0071] In step (3), the metal salt may be one or more selected from silver salts, bismuth salts, iridium salts and platinum salts.
[0072] In step (3), the anion in the metal salt may be nitrate.
[0073] In step (3), the molar ratio of the metal ions in the metal salt to the tannic acid in step (1) can be (5-9):1, for example, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1. In the present invention, controlling the molar ratio of the metal ions in the metal salt to the tannic acid in step (1) within the above range is beneficial to improving the stability and catalytic performance of the electrode material, and is beneficial to improving the voltage efficiency, energy efficiency, charge and discharge energy and cycle performance of the liquid flow battery.
[0074] In step (3), the first mixing method can be one or more selected from ultrasound, stirring and oscillation.
[0075] In step (3), the first mixing time can be 1 to 120 min, for example, 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min.
[0076] In step (3), the vacuuming time can be 1 to 120 min, for example, 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min.
[0077] In step (3), the second mixing method can be one or more selected from ultrasound, stirring and oscillation.
[0078] In step (3), the mixing time of the second step can be 1 to 120 min, for example, 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min.
[0079] In step (3), the drying temperature can be 40-400°C, for example, 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C.
[0080] In step (3), the drying time can be 20 to 720 min, for example, 20 min, 50 min, 100 min, 150 min, 200 min, 300 min, 400 min, 500 min, 600 min, or 700 min.
[0081] In step (4), sintering can be performed in an atmosphere of nitrogen or an inert gas.
[0082] In step (4), the heating rate can be 1~50℃ / min, for example, 1℃ / min, 5℃ / min, 10℃ / min, 15℃ / min, 20℃ / min, 25℃ / min, 30℃ / min, 35℃ / min, 40℃ / min, 45℃ / min, 50℃ / min.
[0083] In step (4), the sintering temperature can be 200-800°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C.
[0084] In step (4), the sintering time can be 0.5~3h, for example, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h.
[0085] Step (4) further comprises cooling to -10-40°C after sintering, for example -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C.
[0086] In step (4), the inert gas may be one or more selected from argon, helium, xenon and neon.
[0087] In step (4), the flow rate of nitrogen or inert gas can be 1-500 mL / min, for example, 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 80 mL / min, 100 mL / min, 150 mL / min, 200 mL / min, 300 mL / min, 400 mL / min, 500 mL / min.
[0088] The present invention provides an electrode material prepared by the preparation method of the present invention and a liquid flow battery comprising the electrode material of the present invention. The electrode material of the present invention has metal nanoparticles on its surface.
[0089] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are conventional methods, reagents and materials in the art, unless otherwise stated. The raw material compounds in the examples can all be purchased from commercial sources. The carbon felt in the examples and comparative examples of the present invention was purchased from Jingu, Liaoyang, with a thickness of 2.5 mm and an area of 15 cm². The bismuth nitrate pentahydrate in the examples and comparative examples of the present invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. The tannic acid in the examples and comparative examples of the present invention was purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0090] Example 1
[0091] In this embodiment, an electrode material containing metal nanoparticles is prepared, and the specific steps are as follows:
[0092] (1) Dissolve 0.8 g of tannic acid in 25 mL of ethylene glycol, ultrasonicate in an ultrasonic cleaner for 5 min, and stir to fully dissolve the tannic acid to obtain a tannic acid solution;
[0093] (2) Place the carbon felt in a tannic acid solution, evacuate for 10 minutes, release the air, evacuate for another 10 minutes, and release the air again, so that the tannic acid solution is fully immersed in the carbon felt; then ultrasonicate the carbon felt in an ultrasonic cleaner for 5 minutes to ensure that the tannic acid is evenly distributed on the carbon felt;
[0094] (3) Add 1.2 g of bismuth nitrate pentahydrate to the reaction system of step (2), ultrasonicate for 5 min, and stir to effectively dissolve the bismuth nitrate pentahydrate; then evacuate for 10 min, release the gas, evacuate for 10 min again, release the gas again, so that the mixed solution is fully immersed in the carbon felt; then ultrasonicate in an ultrasonic cleaner for 15 min to make the coating precursor formed by the reaction of bismuth nitrate pentahydrate and tannic acid evenly distributed on the surface of the carbon felt; finally, take out the carbon felt loaded with the coating precursor, put it into a vacuum drying oven, and dry it at 110° C. for 4 h to obtain an electrode material intermediate;
[0095] (4) The electrode material intermediate is placed in a tubular furnace, argon gas is introduced at a flow rate of 80 mL / min, the temperature is increased to 700°C at a heating rate of 5°C / min, sintered for 90 minutes, and then naturally cooled to 25°C to obtain an electrode material with metal nanoparticles on the surface of the electrode material.
[0096] Example 2
[0097] The other conditions of this example are the same as those of Example 1, except that the mass of bismuth nitrate pentahydrate in step (2) is replaced from 1.2 g to 1.6 g.
[0098] Figure 1-Figure 5 The scanning electron microscope image and X-ray energy spectrum image of the electrode material prepared in Example 2 are shown. Figure 5 The displayed area Figure 4 The displayed area corresponds.
[0099] Example 3
[0100] The other conditions of this example are the same as those of Example 1, except that the mass of bismuth nitrate pentahydrate in step (2) is replaced from 1.2 g to 2.0 g.
[0101] Comparative Example 1
[0102] This comparative example uses carbon felt as the electrode material.
[0103] Comparative Example 2
[0104] The electrode material is prepared in this comparative example, and the specific steps are as follows:
[0105] (1) dissolving 2 g of bismuth nitrate pentahydrate in 25 mL of ethylene glycol, ultrasonicating in an ultrasonic cleaner for 5 min, and stirring to fully dissolve the bismuth nitrate pentahydrate to obtain a bismuth nitrate pentahydrate solution;
[0106] (2) placing the carbon felt in a bismuth nitrate pentahydrate solution, evacuating the carbon felt for 10 minutes, releasing the air, evacuating the carbon felt for 10 minutes, releasing the air, so that the bismuth nitrate pentahydrate solution is fully immersed in the carbon felt; then ultrasonicating the carbon felt in an ultrasonic cleaner for 15 minutes; finally, taking the carbon felt out, placing it in a vacuum drying oven, and drying it at 110° C. for 4 hours to obtain an electrode material intermediate;
[0107] (3) The electrode material intermediate was placed in a tubular furnace, argon gas was introduced at a flow rate of 80 mL / min, the temperature was increased to 200°C at a heating rate of 5°C / min, sintered for 60 min, then the temperature was increased to 700°C at a heating rate of 5°C / min, sintered for 90 min, and finally naturally cooled to 25°C to obtain the electrode material.
[0108] Comparative Example 3
[0109] The electrode material is prepared in this comparative example, and the specific steps are as follows:
[0110] (1) Dissolve 0.8 g of tannic acid in 25 mL of ethylene glycol solution, stir under ultrasonication for 5 min, then add 1.6 g of bismuth nitrate, stir under ultrasonication for 5 min to obtain a mixed solution;
[0111] (2) Place the carbon felt in the mixed solution, evacuate for 10 minutes, release the air, evacuate for 10 minutes, release the air again, so that the mixed solution is fully immersed in the carbon felt; then ultrasonicate it in an ultrasonic cleaner for 15 minutes; finally take it out, place it in a vacuum drying oven, and dry it at 110°C for 4 hours to obtain an electrode material intermediate; (3) Place the electrode material intermediate in a tubular furnace, introduce argon at a flow rate of 80 mL / min, heat it to 700°C at a heating rate of 5°C / min, sinter it for 90 minutes, and then naturally cool it to 25°C to obtain an electrode material.
[0112] Test Example 1
[0113] The electrode materials of Examples 1-3 and Comparative Examples 1-3 were respectively assembled into all-vanadium liquid flow batteries and subjected to characteristic tests (coulombic efficiency, voltage efficiency, energy efficiency, charging energy and discharging energy).
[0114] Preparation of all-vanadium redox flow battery: The effective area of the electrode is 15 cm 2The compression ratio is 35% (here the compression ratio refers to the ratio of the compression amount of the carbon felt to the original carbon felt thickness), and the active substances in the positive and negative electrolytes are V with a concentration of 1.65 mol / L. 4+ and V 5+ and V at a concentration of 1.65 mol / L 2+ and V 3+ The supporting electrolyte is sulfuric acid with a concentration of 4.3 mol / L, the volume of the positive and negative electrolytes is 50 mL, and the diaphragm is a perfluorosulfonic acid proton exchange membrane (thickness is 50 μm, purchased from Kerun).
[0115] Characteristic test: The characteristic test of the all-vanadium redox flow battery assembled with the electrode materials of Examples 1-3 and Comparative Examples 1-5 was carried out using a constant current, and the electric density was 150, 200, 250, 300 and 350, 400 mA / cm 2 The upper limit of charge is 1.55V, the lower limit of discharge is 1.00V, and the battery is cycled 5 times at each current density. The data of the 5th cycle is taken as the initial performance, and the coulombic efficiency, voltage efficiency, energy efficiency, charging energy and discharging energy are obtained. The test results are shown in Tables 1 to 5.
[0116] Table 1: Coulombic efficiency of all-vanadium liquid flow batteries assembled with electrode materials of Examples 1-3 and Comparative Examples 1-3
[0117]
[0118] Table 2: Voltage efficiency of all-vanadium redox flow batteries assembled with electrode materials of Examples 1-3 and Comparative Examples 1-3
[0119]
[0120] Table 3: Energy efficiency of all-vanadium redox flow batteries assembled with electrode materials of Examples 1-3 and Comparative Examples 1-3
[0121]
[0122] Table 4: Charging energy of all-vanadium redox flow batteries assembled with electrode materials of Examples 1-3 and Comparative Examples 1-3
[0123]
[0124] Table 5: Discharge energy of all-vanadium redox flow batteries assembled with electrode materials of Examples 1-3 and Comparative Examples 1-3
[0125]
[0126] Test Example 2
[0127] The electrode materials of Example 2 and Comparative Example 1 were respectively assembled into all-vanadium liquid flow batteries and subjected to cycle performance tests.
[0128] Cycle performance test: The electrode materials of Example 2 and Comparative Example 1 were assembled into an all-vanadium liquid flow battery and subjected to cycle performance test. The current density was 300 mA / cm 2 , the upper limit of charge is 1.55V, the lower limit of discharge is 1.00V, and the cycle is 2000 times. The test results are shown in Table 6.
[0129] Table 6: Cycling performance of all-vanadium redox flow batteries assembled with electrode materials of Example 2 and Comparative Example 1
[0130]
[0131] It can be seen from Tables 1 to 5 that compared with the all-vanadium liquid flow battery assembled with the untreated carbon felt in Comparative Example 1, the all-vanadium liquid flow batteries assembled with the electrode materials treated with tannic acid and metal salts in Examples 1-3 have higher voltage efficiency, energy efficiency, charging energy and discharging energy. This indicates that the treatment of tannic acid and metal salts during the preparation of electrode materials is beneficial to improving the voltage efficiency, energy efficiency, charging energy and discharging energy of the all-vanadium liquid flow battery.
[0132] Compared with the all-vanadium liquid flow battery assembled with electrode materials that have not been treated with tannic acid in Comparative Example 2, the all-vanadium liquid flow battery assembled with electrode materials that have been treated with tannic acid in Examples 1-3 has higher voltage efficiency, energy efficiency, charging energy and discharging energy, which indicates that the addition of tannic acid during the preparation of electrode materials is beneficial to improving the voltage efficiency, energy efficiency, charging energy and discharging energy of the all-vanadium liquid flow battery.
[0133] Compared with the all-vanadium liquid flow battery assembled with electrode materials treated with a mixed solution of tannic acid and metal salts in Comparative Example 3, the all-vanadium liquid flow battery assembled with electrode materials first treated with tannic acid and then treated with metal salts in Examples 1-3 has higher coulombic efficiency, voltage efficiency, energy efficiency and discharge energy. Furthermore, the energy efficiency and coulombic efficiency of the all-vanadium liquid flow battery in Comparative Example 3 are greatly reduced. The reason is presumably that the method of Comparative Example 3 will damage the membrane and thus lead to a decrease in coulombic efficiency. It can be seen that the treatment method of using tannic acid and metal salts in batches during the preparation of electrode materials is beneficial to improving the coulombic efficiency, voltage efficiency, energy efficiency and discharge energy of the all-vanadium liquid flow battery.
[0134] It can be seen from Table 6 that compared with the all-vanadium liquid flow battery assembled with the untreated carbon felt in Comparative Example 1, the all-vanadium liquid flow battery assembled with the electrode material treated with tannic acid and metal salt in Example 2 has better cycle performance, which indicates that the treatment of tannic acid and metal salt during the preparation of electrode materials is beneficial to improving the cycle performance of the all-vanadium liquid flow battery.
Claims
1. A method for preparing a flow battery electrode material, characterized in that: The method comprises the following steps: (1) mixing tannic acid and an organic solvent to prepare a tannic acid solution; (2) soaking the electrode substrate in the tannic acid solution prepared in step (1), evacuating and degassing the solution, and then mixing the solution to load the tannic acid on the electrode substrate; (3) adding the metal salt to the reaction system obtained in step (2), first performing the first step of mixing to dissolve the metal salt, then performing vacuuming and degassing, and then performing the second step of mixing, and then taking out the electrode substrate loaded with the coating precursor and drying it to obtain an electrode material intermediate, wherein the coating precursor is formed by the reaction of the metal salt and tannic acid; (4) sintering the electrode material intermediate obtained in step (3) to obtain a flow battery electrode material; In step (1), the organic solvent is selected from one or more of ethylene glycol, ethanol, acetone, N,N-dimethylformamide, dichloroethane and chloroform, and the mass ratio of the organic solvent to tannic acid is (1-100):1; In step (2), the electrode substrate is carbon felt, graphite felt, carbon cloth, carbon paper or carbon foam; In step (3), the metal salt is a bismuth salt, and the molar ratio of the metal ion in the metal salt to the tannic acid in step (1) is (5-9):1; In step (4), sintering is carried out in an atmosphere of nitrogen or an inert gas, and the sintering temperature is 200-800°C.
2. The method according to claim 1, characterized in that The method has one or more of the following features: In step (1), the mass ratio of the organic solvent to tannic acid is (5-50):1; In step (1), the mixing method is selected from one or more of ultrasound, stirring and oscillation; In step (1), the mixing time is 1 to 120 minutes.
3. The method according to claim 1, characterized in that The method has one or more of the following features: In step (2), the vacuuming time is 1 to 120 minutes; In step (2), the mixing method is selected from one or more of ultrasound, stirring and oscillation; In step (2), the mixing time is 1 to 120 minutes.
4. The method according to claim 1, characterized in that The method has one or more of the following features: In step (3), the anion in the metal salt is nitrate; In step (3), the molar ratio of the metal ion in the metal salt to the tannic acid in step (1) is (6-8):1; In step (3), the first mixing method is selected from one or more of ultrasound, stirring and oscillation; In step (3), the first step mixing time is 1 to 120 minutes.
5. The method according to claim 1, characterized in that The method has one or more of the following features: In step (3), the vacuuming time is 1 to 120 minutes; In step (3), the second mixing method is selected from one or more of ultrasound, stirring and oscillation; In step (3), the second mixing time is 1 to 120 minutes; In step (3), the drying temperature is 40-400°C; In step (3), the drying time is 20 to 720 minutes.
6. The method according to claim 1, wherein: In step (4), the heating rate of the sintering process is 1-50°C / min; and / or In step (4), the sintering time is 0.5~3h.
7. The method according to claim 1, characterized in that In step (4), the inert gas is selected from one or more of argon, helium, xenon and neon; and / or In step (4), the flow rate of nitrogen or inert gas is 1-500 mL / min.
8. A liquid flow battery electrode material, characterized in that: The liquid flow battery electrode material is prepared by the method described in any one of claims 1-7.
9. A liquid flow battery, characterized in that: The liquid flow battery comprises the liquid flow battery electrode material according to claim 8.
Citation Information
Patent Citations
Composite electrode for all-vanadium redox flow battery and preparation method of composite electrode
CN112054215A
Method for preparing graphite felt electrode material loaded with bimetallic particles through reduction method
CN118099459A
Preparation method of polyphenol modified nano-silver carrying antibacterial fabric
CN105839419A
Iron-tannic acid derivative modified graphite felt heterogeneous electro-Fenton cathode material as well as preparation method and application thereof
CN112408668A